The Religious Values in the Nyunatan Tradition of the Bayan Indigenous Community as a Source of Cultural Learning in Lombok - Zulkifli, Zulkifli; Mayasari, Deviana; Winata, Alihardi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
Indonesia is renowned as an archipelagic nation with diverse traditions and many cultural practices. Diversity in Indonesia is prominently displayed on the island of Lombok, particularly in the village of Bayan, North Lombok Regency. This research aims to provide deeper insights into how the traditional practice of Nyunatan (circumcision) among the indigenous people of Bayan, Lombok, can inspire religious and cultural education. This research employs a qualitative method with a descriptive approach. Data collection involved observation, interviews, and documentation. Data analysis followed an interactive analysis model by Miles and Huberman, encompassing data collection, data reduction, data display, and conclusion drawing. The findings reveal that within the tradition of Nyunatan, the indigenous community of Bayan still adheres to traditional methods, utilizing tools like Bango-bango and Ladik, along with traditional herbal treatment, Talas. Furthermore, the Nyunatan tradition embodies many religious values, including beliefs, purity, discipline, exemplariness, and social concern. Each of these values inherent in the Nyunatan tradition can serve as a source of learning for religious and cultural education, particularly in efforts to preserve these values among the younger generation.